2018
DOI: 10.1088/2399-6528/aaf3ec
|View full text |Cite
|
Sign up to set email alerts
|

A polaron approach to photorefractivity in Fe : LiNbO3

Abstract: The thermally activated, incoherent hopping of small electron polarons generated by continuous illumination in iron-doped lithium niobate is simulated by a Marcus-Holstein model for which all the input parameters are known from literature. The results of the calculations are compared with a comprehensive set of data obtained from photorefractive, photogalvanic and photoconductive measurements under green light excitation on samples with different doping levels and stoichiometries in the temperature range betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Also, it is reported that, in LN:Fe, the charge transportation through polaron hopping of electron/holes is slow and is processed on Li-sites due to the presence of Nb Li defects. It was suggested that in the absence of the antisites Nb, the hopping transport is shifted to the Nb sites and is much faster than chaotic Li-sites [42,43,44]. Therefore, doping V and Zr with Fe ions changes the hopping transport to Nb sites by reducing the Nb Li sites and does not disturb the usual lithium site occupation of Fe and instead helps in eliminating the undesired intrinsic traps as shown in Figure 5b.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is reported that, in LN:Fe, the charge transportation through polaron hopping of electron/holes is slow and is processed on Li-sites due to the presence of Nb Li defects. It was suggested that in the absence of the antisites Nb, the hopping transport is shifted to the Nb sites and is much faster than chaotic Li-sites [42,43,44]. Therefore, doping V and Zr with Fe ions changes the hopping transport to Nb sites by reducing the Nb Li sites and does not disturb the usual lithium site occupation of Fe and instead helps in eliminating the undesired intrinsic traps as shown in Figure 5b.…”
Section: Discussionmentioning
confidence: 99%
“…The main contribution to the photovoltaic current arises along the z axis of the material and is almost independent of light polarization since β zxx = β zyy and β zzz are nearly the same size (4 × 10 –8 V –1 ); in contrast, the in-plane contributions to the photovoltaic current along the y axis are practically reduced to one-tenth, since the elements β yxx = β yyy are smaller by almost 1 order of magnitude (2 × 10 –9 V –1 ) . Therefore, photoexcited electrons easily accumulate on the + z face of the Fe:LiNbO 3 crystal, leading to a surface charge density σ c = ϵ zz r ϵ 0 L p v Λ , where ϵ zz r = 28 is the relative dielectric constant along the z axis, ϵ 0 the dielectric constant in vacuum, and L pv and Λ are the mean photovoltaic transport length and the drift coefficient, ,, respectively. According to the values of L pv and Λ reported in the literature, in the sample used in this study, surface charge densities of up to 720 μC/m 2 are expected to be photoinduced, leading to a photovoltaic field inside the crystal of approximately 3 × 10 6 V/m.…”
Section: Methodsmentioning
confidence: 99%
“…Подобный механизм ранее уже обсуждался в рамках модели транспорта фотоиндуцированного электрона по двум типам ловушек в процессе возникновения фоторефракции [1]. Отметим, что в последнее время достаточно активно обсуждается роль ПМР в фоторефрактивном эффекте [27][28][29].…”
Section: анализ и обсуждение результатовunclassified